1961
DOI: 10.1021/jo01064a051
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidines. I. 1-Substituted 3-Pyrrolidinylmethyl Alcohols and Chlorides1

Abstract: Dialkyl itaconate was condensed with various primary amines to form 1-substituted 5-oxo-3-pyrrolidinecarboxylates which were reduced to 1-substituted 3-pyrrolidinemethanols by lithium aluminum hydride. Treatment of these pyrrolidinemethanols with thionyl chloride yielded their corresponding chlorides. 1-Substituted 3-pyrrolidinylmethyl alcohols and chlorides are useful intermediates for the preparation of a number of physiologically active compounds. l-Methyl-3-pyrrolidincmethanol was also prepared from diethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Synthesis of alkyl substituted pyrrolo-thiadiazoles 4a (R = Bn) and 4b (R = Me) started from itaconic acid or its dimethylester ( Scheme 2 ). Cyclization towards the pyrrolidine system 5a/b was optimized based on a protocol by Feldkamp and coworker [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of alkyl substituted pyrrolo-thiadiazoles 4a (R = Bn) and 4b (R = Me) started from itaconic acid or its dimethylester ( Scheme 2 ). Cyclization towards the pyrrolidine system 5a/b was optimized based on a protocol by Feldkamp and coworker [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…NaHCO 3 -solution, and repeatedly extracted with dichloromethane. The combined organic layers were washed with water, dried over sodium sulfate, and concentrated to give 56.92g (88% overall) of 5a [ 11 ] as colorless crystals; m.p. 71-73°C; 1 H-NMR (CDCl 3 ): 2.90-3.10 (m, 2H, H-4), 3.18-3.37 (m, 1H, H-3), 3.58 (d, J=8Hz, 2H, H-2), 3.69 (s, 3H, OCH 3 ), 4.45-4.50 (m, 2H, PhCH 2 ), 7.14-7.38 (m, 5H, arom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another class of itaconic acid-based solvents are the N-alkyl-4-carboxypyrrolidinone esters (NACP), for which synthesis from itaconic acid was described by Wu et al as early as in 1961. 78 The experimental synthesis is a two-step procedure (esterification followed by a one-pot amine addition and cyclic amide formation), while the GRASS pathway decomposes it into three virtual transformations. It should be noted that both experimentally and virtually, the first two steps can be switched and still lead to the obtention of NACP (no.…”
Section: Transformation Of Itaconic Acid Into Virtual Solventsmentioning
confidence: 99%
“…5 Atigadda et al 6 reported a substituted 2-pyrrolidinone that was a low nanomolar inhibitor of neuraminidase. Wu and Feldkamp 7 utilized a pyrrolidinone as a scaffold in a novel selective inhibitor of matrix metalloproteinases (MMPs).…”
Section: Introductionmentioning
confidence: 99%